1994
DOI: 10.1080/10408399409527655
|View full text |Cite
|
Sign up to set email alerts
|

A report of the proceedings of an MSG workshop held august 1991

Abstract: This report of the proceedings of a workshop on monosodium glutamate (MSG) represents the output of an exchange of scientific information, discussed and debated, by a group of experts representing a variety of disciplines. Experts in the areas of food science, potential adverse reactions to foods, pharmacology, neuroscience, biochemistry, nutrition, pediatrics, and anatomy reviewed the current scientific literature relative to the safe use of MSG in foods. These proceedings supplement the extensive literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…Glutamate is rapidly metabolized by enterocytes and hepatocytes, and studies have shown that even when MSG is administered in quantities much larger than a typical dietary intake (430 mg/kg/day), serum levels are only slightly and transiently elevated [6].…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate is rapidly metabolized by enterocytes and hepatocytes, and studies have shown that even when MSG is administered in quantities much larger than a typical dietary intake (430 mg/kg/day), serum levels are only slightly and transiently elevated [6].…”
Section: Introductionmentioning
confidence: 99%
“…Monosodium glutamate (MSG) is a food additive that is currently considered to be without serious safety concerns (Filer and Stegink, 1994). Initially, elevated consumption of MSG was linked to the symptoms such as headache, burning sensations, facial pressure and chest tightness (Schaumburg et al, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate or glutamic acid is in the same amino acid family group as glutamine. Glutamate is a major component of most natural protein foods such as meat, fish, milk, and some vegetables that play an essential role in human metabolism (Filer & Stegink, ; Fernstrom, ). It helps transmit messages around the brain and also reduce chest pain commonly associated with coronary heart disease (Niswender & Conn, ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is a major component of most natural protein foods such as meat, fish, milk, and some vegetables that play an essential role in human metabolism (Filer & Stegink, 1994;Fernstrom, 2000). It helps transmit messages around the brain and also reduce chest pain commonly associated with coronary heart disease (Niswender & Conn, 2010 (53.430 g/100 g), and K (4.234 g/100 g) were the most prominently appreciable vitamins present in D. dewerei leaves which were far more than the quantity of each of the vitamins in the fruits of the plant (Table 3).…”
Section: Discussionmentioning
confidence: 99%